Gambaran Kinerja Bidan pada Pelayanan Antenatal Care di Puskesmas Dasan Agung Kota Mataram Tahun 2023 - Wardana, Lalu Muhammad Fikri; Herawati, Yennike Tri (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2023)
Background: Maternal mortality is still a health problem in Indonesia. Antenatal care as a form of prevention program to prevent maternal death. The low coverage of ANC services can be caused by midwives' poor performance in providing services. Permenkes Number 4 of 2019 concerning Health SPM, the performance achievements of district/city regional governments in providing ANC services are assessed from the coverage of health services for pregnant women according to standards in their working areas. Based on Presidential Regulation Number 18 of 2020, the percentage that must be achieved in ANC service coverage is 95%, while data from the NTB Provincial Health Office, the coverage of antenatal care services in Mataram City is below this target with an average K1 and K4 from 2019 - 2021 is 92.67% and 81.66%. Dasan Agung Health Center is a health center located in the city of Mataram, with an average coverage of antenatal care services for K1 and K4 which is still below standard, namely 78.5% for K1 and 60.1% for K4.Aims: the purpose of this study was to determine the factors related to performance in antenatal care services at the Dasan Agung Community Health Center, Mataram City. Method: descriptive research design, the number of samples is 11 people with total sampling. Results: the human resource and leadership variables at the Dasan Agung Health Center tend to be good, the reward and organizational structure variables tend to be quite good. Meanwhile for the performance variable, it was found that the performance of midwives at the Dasan Agung Health Center tended to be good. Conclusion: the results of the study show that the majority of midwives at the Dasan Agung Health Center in Mataram City have good performance in providing antenatal care services